A color vision approach considering Reflection Co efficient based on Autoencoder techniques using deep neural networks - Mahmud, Shakib Izaz; Shovon, Sartaz Islam; Hasnat, Md. Abrar; Na s, Md. Fahim (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.